(untitled) - Sachs, Jonah (Boston, Mass., 2012)
Winning the Story Wars is a call to arms for business communicators to cast aside broken traditions and join a revolution to build the iconic brands of the future. It puts marketers in the role of heroes with a chance to transform not just their craft but the enterprises they represent. After all, success in the story wars doesn’t come just from telling great stories, but from learning to live them.
Keywords: Tiếp thị,Marketing; Khía cạnh xã hội,Social aspects